Changes in Soviet and post-Soviet Indigenous diets in Chukotka - Kozlov, Andrew; Nuvano, Vladislav; Vershubsky, Galina (Études/Inuit/Studies, 2007)
AbstractAn analysis of changing diet patterns during the Soviet and post-Soviet periods was carried out among sea mammal hunters (villages of Lorino and Lavrentiya) and reindeer herders (village of Vaegi) of Chukotka. Economic and ethnic factors in the choice of food were investigated. The results show that both studied groups are developing diets that substantially differ from both the traditional and the “Soviet” ones.